Analysis of Marketing Strategy to Increase the Number of Students at Primagama Educational Institution Bengkulu Branch - Samsul Akmal; Solichin Solichin (Penerbit Jurnal Indonesia, 2021)
This study aims to re-analyze the marketing strategy carried out by Primagama educational institutions in order to increase the number of students. The analytical method used in this research is SWOT analysis. SWOT is an acronym for the initial letters, namely Strengths (strengths), Weaknesses (weaknesses), Opportunities (opportunities) and Threats (Threats). SWOT analysis can be processed if internal factors have been obtained, namely Strengths (S) and Weaknesses (W), external factors Opportunity (O) and Threats (T). From the results of processing the questionnaire data and other data, it is found that the point in quadrant I in the SWOT diagram means that Primagama Bengkulu branch is in a very favorable situation. Primagama Bengkulu branch has great opportunities and strengths so that they can take advantage of existing opportunities. The strategy applied in this condition is to support an aggressive policy (growth oriented strategy.